Alternative Proteins, Meat and Dairy Analogues: Are They Viable Consumer Options? - Christina Rehagel; Diana Bogueva; Dora Marinova; Sümeyye Uçak; Esra Çelik; İsmail Hakkı Tekiner; Ömer Akıneden (Diponegoro University, 2026)
The increasing production and consumption of meat globally have raised serious concerns about environmental pollution, land and water requirements, greenhouse gas emissions, biodiversity loss and human health. Ensuring adequate protein requirement is one of the biggest challenges to food security. Therefore, new-generation meat and dairy analogues from a wide range of novel protein sources, such as upcycled plant materials, cultured cells, fermentation processes, fungi, algae and edible insects, have gained significant interest from both researchers and consumers. This study aims to review alternative proteins, meat and dairy analogues, and assesses their potential for an affordable, health-conscious, environmentally responsible and sustainable food future for humanity. The findings reveal that for the fourth industrial revolution in food production to successfully drive a protein transition, consumers must be engaged from the outset — including in the marketing of new products — to prevent rejection and resistance to dietary change. Clear and compelling communication is also needed to explain why and how novel meat and dairy alternatives surpass direct plant-based options, which have long offered significant benefits and remain a reliable and satisfying food choice.